Madrasah-Based Management (MBM) In Improving The Quality Of PTK At Madrasah Ibtidaiyah Al-Azhar Menganti Gresik - Suprayitno (Journal of Social Science and Economics, 2022)
The context of this research stems from the accreditation results of MI Al-Azhar Menganti Gresik on the standard of educators and education staff (PTK) showing a score of 84. This score is the lowest score when compared to other standards. This study aims to describe the planning, implementation and supervision in improving the quality of PTK at MI Al-Azhar Menganti Gresik. This research is a type of qualitative research with a case study approach. The background of this research was at MI Al-Azhar Menganti Gresik with the research subject being the head of the madrasa, deputy head of the madrasa, PTK. While data collection techniques using observation techniques, interviews and documentation. The data obtained were then analyzed using the Miles, Huberman and Saldan models through four stages: data collection, data condensation, data presentation and drawing conclusions. The results of the research and discussion show: 1) Planning in Madrasah-Based Management (MBM) is prepared based on the principles of fairness, partnership, independence, efficiency and accountability. 2) Implementation in MBM is carried out based on the principles of fairness, independence, partnership, participation and accountability. 3) Supervision in MBM is carried out based on the principle of accountability.